Modified Halterman Appliance for management of ectopically erupting permanent molar: A case report - Saraswathi V Naik; Simin Kittur; Basappa Nadig; Sindhushree GS; Amitha M Shagale (Arbu Academic Publishing, 2023)
Ectopic eruption is a disturbance in the eruptive path of a tooth in an abnormal position leading to many local problems, such as premature loss of the second primary molars, space loss, increased prevalence of dental caries, supra-eruption of the opposing molars, a mesial inclination of the permanent maxillary first molars, and class II molar relationship. The present case report describes the management of an ectopically erupting mandibular first molar in an 8-year-old child with a modified Halterman appliance. Halterman appliance was modified by incorporating cross-arch anchorage. Follow-up was carried out at 1 month, 3 months,6 months, and 9 months until distalization of the molar was achieved. Space analysis was carried out and a fixed functional space maintainer was cemented which was followed up at 12 months. According to the present case report, a modified Halterman appliance is an effective appliance in achieving distalization of an ectopically erupting permanent molar in a mixed dentition period.